Java 6 - Griffith, Arthur; Virtual Training Company ([Autralia] : Virtual Training Company, 2008)
This course describes 184 running programs showing how the new features work. VTC author Arthur Friffith builds on current Java knowledge by detailing these advanced features with simple explanation
Title from container
Contains 92 movies with total time 7 hours
Training CD
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Java (Computer program language); Programming languages (Electronic computers)